Some possible shapes of the U-smile plot. - Barbara Więckowska (536264) (2025)
The U-smile plot of the BA or RB coefficients represents the effect of adding a new variable to a reference model. Its shape can indicate improved prediction for both classes (double smile – panel a) or either class with no changes in the other (smile + flat line, flat line + smile – panels b and c). It can also show worsened prediction for both classes (double frown - panel d) or either class with no changes in the other (frown + flat line, flat line + frown – panels e and f). A flat line of the entire U-smile plot indicates no change in prediction for both classes (double flat line – panel g), while a zigzag pattern shows improved prediction for one class and worsened prediction for the other (smile + frown, frown + smile – panels h and i).